A method for normal-mode-based model reduction in nonlinear dynamics of slender structures. (15th October 2015) - Wang, Yinan; Palacios, Rafael; Wynn, Andrew
Highlights: A non-intrusive approach to construct geometrically-nonlinear models of large structures with slender subcomponents from existing industrial-scale linear vibration FE models. An extension of static condensation methods on slender structures that utilises the spatial distribution of the condensation nodes. A numerical procedure to filter high-frequency dynamics while retaining the contribution of the high-frequency mode shapes to approximate large deformations. A numerically-efficient modal projection of geometrically-nonlinear structural dynamics. Abstract: This paper introduces a nonlinear reduced-order modelling methodology for finite-element models of structures with slender subcomponents and inertia represented by lumped masses along main load paths. The constructed models have dynamics described by 1-D intrinsic equations of motion, which are further written in modal co-ordinates. This yields finite-dimensional approximations of the system dynamics with only quadratic nonlinearities. Evaluation of the problem coefficients is performed from static condensation of the original model on the lumped masses. The method exploits the multi-point constraints typically used to obtain sectional loads in aircraft aeroelastic analysis. The technique is illustrated on simple 3D structural models built using solid elements.